Development of Biology Learning Media Video Tutorial - GH, Muliana (Budapest International Research and Critics University, 2022)
This research is a research and development which aims toproduce valid biology tutorial video learning media. This research was conducted using a 4D development model from Thiagarajan, with the Define, Design, Development, and Disseminate stages involving two expert validators and one practitioner validator. The instrument used is a validation instrument sheet. The data collection technique is that the validation sheet is distributed to the validator to get the value of the validation of the development of learning media. The data obtained were analyzed using the validity criteria according to Yamasari. The results of the study indicate that the -based learning mediaCamtasia Studio software has high validity. The results of the media validity research are shown based on hthe validation results from expert and practitioner validators are the average value of validity for the material aspect 3.82 = valid and the average value of validity for the media format aspect is 3.78 = valid. The average value of the total validity of Camtasia Studio is RTV = 3.80 and is included in the valid category. Based on the results of this study, it can be concluded that the Camtasia Studio-based learning media produced is valid so that it is feasible to use.